Do Pension Benefits Accelerate Cognitive Decline? Evidence from Rural China - Plamen Nikolov; Md Shahadath Hossain (Institute of Labor Economics (IZA), 2022)
Economists have mainly focused on human capital accumulation, rather than on the causes and consequences of human capital depreciation in late adulthood. To investigate how human capital depreciates over the life cycle, we examine how a newly introduced pension program, the National Rural Pension Scheme, affects cognitive performance in rural China. We find significant adverse effects of access to pension benefits on cognitive functioning among the elderly. We detect the most substantial impact of the program on delayed recall, a cognition measure linked to the onset of dementia. In terms of mechanisms, we find that cognitive deterioration in late adulthood is mediated by a substantial reduction in social engagement, volunteering, and activities fostering mental acuity.
Keywords: H55; J24; I31; O12; J26; J14; H75; 330; middleincome countries; cognition; cognitive functioning; human capital; life cycle; LMICs; developing countries